2012
DOI: 10.1073/pnas.1121134109
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor WRKY23 assists auxin distribution patterns during Arabidopsis root development through local control on flavonol biosynthesis

Abstract: Gradients of the plant hormone auxin, which depend on its active intercellular transport, are crucial for the maintenance of root meristematic activity. This directional transport is largely orchestrated by a complex interaction of specific influx and efflux carriers that mediate the auxin flow into and out of cells, respectively. Besides these transport proteins, plant-specific polyphenolic compounds known as flavonols have been shown to act as endogenous regulators of auxin transport. However, only limited i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
147
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(165 citation statements)
references
References 52 publications
6
147
0
Order By: Relevance
“…In this article, we found that the auxin pathway was compromised in the exb1-D mutant, as shown by auxin reporter DR5-GUS analysis and by the reduced rates of hypocotyl elongation of exb1-D in high temperature treatment. This is consistent with the fact that overexpression of WRKY23 disrupts auxin transport and response (Grunewald et al, 2012). Auxin is a well-known inhibitor of bud outgrowth and an auxin minimum is required for AM initiation (Hayward et al, 2009;Stirnberg et al, 2012;Y.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In this article, we found that the auxin pathway was compromised in the exb1-D mutant, as shown by auxin reporter DR5-GUS analysis and by the reduced rates of hypocotyl elongation of exb1-D in high temperature treatment. This is consistent with the fact that overexpression of WRKY23 disrupts auxin transport and response (Grunewald et al, 2012). Auxin is a well-known inhibitor of bud outgrowth and an auxin minimum is required for AM initiation (Hayward et al, 2009;Stirnberg et al, 2012;Y.…”
Section: Discussionsupporting
confidence: 66%
“…WRKY23 acts downstream of IAA14, AUXIN RESPONSE FACTOR7 (ARF7), and ARF19 (Grunewald et al, 2008(Grunewald et al, , 2012. WRKY23 also controls auxin distribution by regulating flavonol biosynthesis during plant root and embryo development (Grunewald et al, 2012(Grunewald et al, , 2013. In this article, we found that the auxin pathway was compromised in the exb1-D mutant, as shown by auxin reporter DR5-GUS analysis and by the reduced rates of hypocotyl elongation of exb1-D in high temperature treatment.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Similarly, auxin transport phenotypes in several Arabidopsis flavonoid mutants have been linked to altered accumulation of flavonoid glycosides as they contain undetectable levels of free kaempferol or quercetin aglycones (Buer et al, 2013). In addition, overexpression of the transcription factor WRKY23 in Arabidopsis led to increased levels of quercetin-3-O-rhamnoside, accompanied by a reduced auxin transport in seedling roots (Grunewald et al, 2012). Among the 18 cytokinin-inducible flavonoid-related genes, 14 were putative (iso)flavonoid glycosyl transferases (Ariel et al, 2012;Supplemental Table 2).…”
Section: Flavonoids Rescue Nodulation In the Cre1 Mutantmentioning
confidence: 99%
“…However, some of the genes belongs to WRKY and myb gene family, known to take part in root development, were found in root specific library. WRKY is required for the growth of roots by stimulating synthesis of flavonols, an endogenous regulators of auxin transport (Grunewald et al 2012) and later has a role in root growth of legumes (Volpe et al 2013). In contrast, a gene encoding for Lysine-specific histone demethylase (KDM1), which is involved in transcriptional repression of root genes via demethylation of histones was also identified in ESTs library probably required for tight regulation of temporal genes (Krichevsky et al 2011).…”
Section: Discussionmentioning
confidence: 99%